Monitoring of mycotoxin biomarkers in the Czech Republic - Ostry, V; Malir, F; Roubal, T; Skarkova, J; Ruprich, J; Cerna, M; Creppy, E E (Mycotoxin research, 2005)
AFM1 was determined in 72 (72%) samples of human urine, range 19-6064 pg/g creatinine, mean 367 pg/g creatinine, median 158 pg/g creatinine and 90% percentile 755 pg/g creatinine in 1997. AFM1 was determined in 46 (43.8%) samples of human urine, range 21-19219 pg/g creatinine, mean 414 pg/g creatinine, median 96 pg/g creatinine and 90% percentile 415 pg/g creatinine in 1998. OTA was determined in 2077 (94.2%) samples of human serum, range 0.1-13.7 μg/L, mean 0.28 μg/L, median 0.2 μg/L and 90% percentile 0.5 μg/L in 1994-2002. OTA was determined in 12 (40%) samples of human kidneys, range 0.1-0.2 μg/kg, mean 0.07 μg/kg, and median 0.05 μg/kg in 2001.